Legacy Effects on the Recovery of Soil Bacterial Communities from Extreme Temperature Perturbation - Jurburg, Stephanie D.; Nunes, Inês; Brejnrod, Asker; Jacquiod, Samuel; Priemé, Anders; Sørensen, Søren J.; Van Elsas, Jan Dirk; Salles, Joana F. (Frontiers in Microbiology, 2017)
The type and frequency of disturbances experienced by soil microbiomes is expected to increase given predicted global climate change scenarios and intensified anthropogenic pressures on ecosystems. While the direct effect of multiple disturbances to soil microbes has been explored in terms of function, their effect on the recovery of microbial community composition remains unclear. Here, we used soil microcosm experiments and multiple model disturbances to explore their short-term effect on the recovery of soil microbiota after identical or novel stresses. Soil microcosms were exposed to a heat shock to create an initial effect. Upon initial community recovery (25 days after stress), they were subjected to a second stress, either a heat or a cold shock, and they were monitored for additional 25 days. To carefully verify the bacterial response to the disturbances, we monitored changes in community composition throughout the experiment using 16S rRNA gene transcript amplicon sequencing. The application of a heat shock to soils with or without the initial heat shock resulted in similar successional dynamics, but these dynamics were faster in soils with a prior heat shock. The application of a cold shock had negligible effects on previously undisturbed soils but, in combination with an initial heat shock, caused the largest shift in the community composition. Our findings show that compounded perturbation affects bacterial community recovery by altering community structure and thus, the community’s response during succession. By altering dominance patterns, disturbance legacy affects the microbiome's ability to recover from further perturbation within the 25 days studied. Our results highlight the need to consider the soil’s disturbance history in the development of soil management practices in order to maintain the system’s resilience.